Evaluation of an Antibiotic Cocktail for Fecal Microbiota Transplantation in Mouse - Tan, Jijun; Gong, Jiatai; Liu, Fengcheng; Li, Baizhen; Li, Zhanfeng; You, Jiaming; He, Jianhua; Wu, Shusong (Frontiers in Nutrition, 2022)
Objective This study aimed to evaluate the effect of an antibiotic cocktail on gut microbiota and provide a reference for establishing an available mouse model for fecal microbiota transplantation (FMT) of specific microbes. Design C57BL/6J mice (n = 24) had free access to an antibiotic cocktail containing vancomycin (0.5 g/L), ampicillin (1 g/L), neomycin (1 g/L), and metronidazole (1 g/L) in drinking water for 3 weeks. Fecal microbiota was characterized by 16S rDNA gene sequencing at the beginning, 1st week, and 3rd week, respectively. The mice were then treated with fecal microbiota from normal mice for 1 week to verify the efficiency of FMT. Results The diversity of microbiota including chao1, observed species, phylogenetic diversity (PD) whole tree, and Shannon index were decreased significantly (P < 0.05) after being treated with the antibiotic cocktail for 1 or 3 weeks. The relative abundance of Bacteroidetes, Actinobacteria, and Verrucomicrobia was decreased by 99.94, 92.09, and 100%, respectively, while Firmicutes dominated the microbiota at the phylum level after 3 weeks of treatment. Meanwhile, Lactococcus, a genus belonging to the phylum of Firmicutes dominated the microbiota at the genus level with a relative abundance of 80.63%. Further FMT experiment indicated that the fecal microbiota from the receptor mice had a similar composition to the donor mice after 1 week. Conclusion The antibiotic cocktail containing vancomycin, ampicillin, neomycin, and metronidazole eliminates microbes belonging to Bacteroidetes, Actinobacteria, and Verrucomicrobia, which can be recovered by FMT in mice.